Up- and down-regulation of membrane receptors as possible mechanisms related to the antiulcer actions of milk in rat gastric mucosa. Issue 2 (February 1987) - Gespach, C.; Emami, S.; Chastre, E.; Launay, J.-M.; Rosselin, G.
Abstract : The effects of a cow's milk diet on receptor activity and histamine metabolism in gastric glands and mucosa isolated from adult rats were examined. The milk diet was associated with (1) a decreased mobilization of H2 receptors by histamine and (2) an increased mobilization of PGE2 (prostaglandin E2 ) receptors in mucous cells (cytoprotective effect) and parietal cells (antiacid effect). These changes are not observed for the receptors reducing pentagastrin- and histamine-induced gastric acid secretion (pancreatic/enteroglucagons, somatostatin) and stimulating mucus, bicarbonate and pepsin secretions in the rat (secretin). Cimetidine produced a parallel displacement of the histamine dose-response curve, suggesting competitive inhibition between this classical H2 receptor antagonist and histamine in the two experimental groups. Prostaglandins and other components in milk such as EGF (epidermal growth factor) and somatostatin might therefore protect gastric mucosa by a differential control of PGE2 and histamine H2 receptor activity either directly (PGE2 in milk) or indirectly (inhibition of endogeneous histamine synthesis/release and stimulation of PGE-I synthesis/release).